(untitled) (Економіка і регіон/ Economics and region, 2024)
Engineering as a sector of the market economy arose a century and a half ago in Great Britain, when the services of engineers, in demand by industrialists for the construction of new factories and the modernization of existing ones, began to be sold for the first time. In this regard, engineering was understood as the provision of services for the creation and operation of industrial facilities and infrastructure. Market size represents the revenue generated from various types of services such as product development, process engineering, automation related services and asset management related services offered by market players. The article reveals the essence of engineering and identifies groups of services of companies providing engineering consultations, defines the subject area and specific practical problems, the solution of which is engineering; the functional dependencies of participants in engineering activities in construction are indicated. The tasks, subject area and classification of engineering in construction are presented, taking into account the main stages of the implementation of an investment and construction project. The place of the engineering company in the system of interaction between participants in investment and construction activities is indicated. The need for a clear definition and delimitation of the functions of participants in engineering activities in construction in order to comply with contractual discipline is shown. Thereafter, by examining the activities of contemporary engineering consulting organizations, the evolution of ASCE guidelines under current engineering law was highlighted. The article attributes success only to the application of these tactics, that is, dependence on the components of modern state law and the use of advanced technologies in construction. All this allows us to significantly expand the volume of construction work in the country and stimulate the use of innovation. It is indicated that the significance of the results obtained for the construction industry lies in a comprehensive analysis as an integral part of investment and construction activities, as well as in determining the range of participants and the nature of their functional dependence. This is necessary to identify the potential for development and improvement of the engineering system in construction.